The neutrality of money reconsidered: A statistical equilibrium model of the labor market - Ellis Scharfenaker; Duncan K. Foley (The University of Utah, Department of Economics, 2023)
Economic analysis has approached the problem of the neutrality of money through methods of supply-demand equilibrium in which changes in aggregate demand due to monetary or fiscal policy are equivalent to changes in the denomination of the monetary standard. We re-examine this question using statistical equilibrium methods adapted from statistical physics, which address both the central tendency of prices in equilibrium and the systematic fluctuation of prices around the central tendency. From this perspective the neutrality of money in the sense of the invariance of real economic outcomes to aggregate demand shocks depends on the adjustment of both expectations of the average level of wages and prices and the further adjustment of anticipations of the scale of fluctuations in prices and wage offers. We illustrate these conclusions through a model of wage and employment outcomes in a labor market model comprised of informationally constrained workers and employers whose interactions have a non-zero impact on wages. The model endogenizes employment interactions between workers and employers in terms of a quantal response equilibrium and produces an equilibrium level of unemployment as a statistical feature of a decentralized labor market. Shocks to the economy can produce short-run increases in involuntary unemployment arising from inertia in the adjustment of expectations. Even after agents align their expectations with market outcomes, unless they also adjust their expectations of the scale of statistical fluctuations in wages, a negative shock to demand can result in higher levels of equilibrium unemployment. In this way the model exhibits a particular type of non-neutrality of money in the short-run and long-run.
Keywords: C18; D80; E10; E24; E70; 330; Neutrality of money; Wage distribution; Labor market; Involuntary unemployment; Statistical equilibrium